Performance Optimization of Slotted Blades for Low-Specific Speed Centrifugal Pumps. (5th January 2023) - Ke, Qidi; Tang, Lingfeng
Abstract : Centrifugal pumps are widely used for the transport of fluids, but low-specific-speed centrifugal pumps widely have problems with serious backflow and low efficiency. In this paper, a low-specific-speed centrifugal pump with a specific speed of 55 is used as a research object. By combining numerical simulation and orthogonal experiment, the pressure distribution and velocity distribution of the flow channel are analyzed, the priority of each geometric factor for slits on pump performance is determined, the geometric parameter structure of the slotted blade is optimized by entropy weight on TOPSIS, the optimal impeller slit solution is obtained. The results show that with a balance of head and efficiency, the order of influence of the factors is: slit center width b > diameter of slit D > shrinkage ratio of slit f > depth of slit h > deflection angle of slit β . The optimal combination of slit geometry parameters is: slit center width is 3 m m, diameter of the slit is 200 m m, shrinkage ratio of the slit is 0.5, depth of the slit is 6 m m, and the deflection angle of the slit is 20°. Through ANSYS FLUENT simulation and experiment of closed pump experiment system, confirmed that hydraulic performance is improved.